Identification of unusual peptides with new Cys frameworks in the venom of the cold-water sea anemone Cnidopus japonicus. Issue 1 (December 2017) - Babenko, Vladislav; Mikov, Alexander; Manuvera, Valentin; Anikanov, Nickolay; Kovalchuk, Sergey; Andreev, Yaroslav; Logashina, Yulia; Kornilov, Daniil; Manolov, Alexander; Sanamyan, Nadya; Sanamyan, Karen; Kostryukova, Elena; et al.
Abstract Sea anemones (Actiniaria) are intensely popular objects of study in venomics. Order Actiniaria includes more than 1, 000 species, thus presenting almost unlimited opportunities for the discovery of novel biologically active molecules. The venoms of cold-water sea anemones are studied far less than the venoms of tropical sea anemones. In this work, we analysed the molecular venom composition of the cold-water sea anemoneCnidopus japonicus . Two sets of NGS data from two species revealed molecules belonging to a variety of structural classes, including neurotoxins, toxin-like molecules, linear polypeptides (Cys-free), enzymes, and cytolytics. High-throughput proteomic analyses identified 27 compounds that were present in the venoms. Some of the toxin-like polypeptides exhibited novel Cys frameworks. To characterise their function in the venom, we heterologously expressed 3 polypeptides with unusual Cys frameworks (designated CjTL7, CjTL8, and AnmTx Cj 1c-1) inE. coli . Toxicity tests revealed that the CjTL8 polypeptide displays strong crustacean-specific toxicity, while AnmTx Cj 1c-1 is toxic to both crustaceans and insects. Thus, an improved NGS data analysis algorithm assisted in the identification of toxins with unusual Cys frameworks showing no homology according to BLAST. Our study shows the advantage of combining omics analysis with functional tests for active polypeptide discovery.